Probing adhesive interactions of self-assembled monolayers of Biphenyldithiol on Au(111): molecular dynamics simulation of force-distance measurements in atomic force microscopy. Issue 3 (3rd July 2022) - Dirama, Taner E.
ABSTRACT: This paper presents an investigation of atomic force microscopy (AFM) in the force-distance mode for self-assembled monolayers (SAM) by means of molecular dynamics modeling methods. A model system of SAM of biphenyldithiol (BPDT) on a gold substrate and a gold tip with a diameter of 10 nm were used. This work has reproduced the general behavior of force–distance curves in similar systems observed in experimental studies. The impact of the structural order (i.e., standing up ordered, disordered and striped phases) on the attractive and repulsive molecular interactions and conformations were revealed. The ordered SAM in standing up phase has the highest adhesive force and the striped phase has the lowest. The adhesive forces as a function of the tip-surface distance exhibit some unique and distinct features. An AFM induced ordering for both disordered and striped phases is reported.